PENGARUH FAKTOR PERSONAL, PERSEPSI DUKUNGAN SOSIAL, PERSEPSI DUKUNGAN ORGANISASI TERHADAP KESEDIAN DIRELOKASI. STUDI KASUS PADA PEGAWAI BPK RI PERAWAKILAN PROVINSI SULAWESI TENGGARA - Muh. Kamaruddin Jamal; Nurwati Nurwati; Muh. Masri; Nursaban Rommy; Enny Wati; Putu Sumarniwati (Pascasarjana Universitas Halu Oleo, 2020)
The purpose of this study was to determine the effect of Personal Factors, Perceived Social Support, and Perceived Organizational Support on Willingness to be Relocated. This research was conducted at BPK RI Representatives of Southeast Sulawesi Province with a total sample of 90 respondents. The sampling technique in this study was carried out by means of the census technique so that the entire population was used as the research sample. The research data were collected using interviews and questionnaires. The analysis technique uses multiple linear regression analysis with the help of SPSS software.. The results showed that: 1) Personal Factor has a significant effect on willingness to be relocated. 2) Perceived Social Support has a significant effect on willingness to be relocated. 3) Perceived Organizational Support has no effect on willingness to be relocated. Simultaneously these variables have a significant effect on willingness to be relocated